Karyotype of Four Species of Pines Naturally Occurring in India - Upadhaya, L. P.; Kedharnath, S. (Indian Forester, 1970)
Karyotypes have been reported for the lour Indian species of Pinus, viz., P. roxburghii, P. insularis, P. wallichiana and P. gerardiana, P. roxburghii has two pairs of secondarily constricted chromosomes and the shortest pair (12th) has heterobrachial arms. P. insularis has two pairs of secondarily constricted chromosomes but two pairs of chromosome. (11th and 12th) have heterobrachial arms. P. wallichiana has only one pair (12th) with heterobrachial arms and no chromosome has secondary constriction. P. gerardiana has two pairs of chromosomes (11th and 12th) with heterobrachial arms like in P. insularis but none of the chromosome is secondarily constricted. On the basis of relative chromosomal length, the discriminant analysis showed that P. insularis is karyotypically distinct from the other three species, viz., P. roxburghii, P. wallichiana and P. gerardiana which form one single cluster.